STRATEGI MANAJEMEN KONFLIK DALAM MENINGKATKAN KEHARMONISAN PENDIDIK DAN TENAGA KEPENDIDIKAN DI PONDOK PESANTREN AL MANDILY - Lanni Jurriah; Irma Suryani Siregar; Sapirin (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This research is motivated by the importance of maintaining harmonious working relationships between educators and educational staff in a pesantren environment, which is characterized by collective life, a hierarchical structure, and dynamic social interactions. The purpose of this study is to identify the forms of conflict that occur, analyze their underlying causes, and examine the conflict management strategies implemented to create a harmonious work environment at Pondok Pesantren Al Mandily.This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The data sources consist of the mudir (leader), educators, and educational staff. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that: (1) The forms of conflict identified include interpersonal conflicts, such as disagreements in scheduling and differences in understanding individual responsibilities; and intergroup conflicts, such as disparities in adapting to technological changes and ineffective communication. (2) The main causes of conflict include differing views on task implementation, unequal dissemination of information, limited technological proficiency among senior educators, and lack of educator involvement in the scheduling process. (3) The strategies applied include open deliberation, one-on-one discussions, improved formal communication, and the instillation of professionalism and responsibility based on Islamic values.This research affirms that conflict management sensitive to local, spiritual, and social values is crucial for maintaining organizational harmony within the pesantren setting.